Sociotechnical System Safety: Hierarchical Control versus Mindfulness. Issue 4 (11th August 2017) - Lintern, Gavan; Kugler, Peter N.
ABSTRACT: Both the hierarchical control model of organizational processes in a sociotechnical system and organizational mindfulness have been promoted, largely through independent lines of argument, as having potential to improve safety in large‐scale sociotechnical systems. We review the arguments to assess the confidence we might place in these claims and to assess whether these views are necessarily incompatible or could be complementary. Our analysis reveals a lack of consistency in the arguments for hierarchical control. It remains unclear whether application of this model to sociotechnical system design will enhance safety or will even degrade it by promoting micromanagement. We conclude that the type of mindfulness that bolsters important safety‐related cognitive processes is just what is missing from the hierarchical control model. The safety of large‐scale sociotechnical systems with catastrophic potential poses an enormous challenge. A functional model with some hierarchical properties, when complemented with insights relating to organizational mindfulness, offers an innovative way of working toward resolving that challenge.